Low-velocity collisions of chondrules: how a thin dust cover helps enhance the sticking probability - Gunkelmann, Nina; Dullemond, Cornelis (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 16.10.2017